A Prospective Study to Find the Association of Low Pregnancy Associated Plasma Protein- A Levels in Early Pregnancy with Adverse Maternal and Fetal Outcome in Pregnant Women - Nishtha Arora, Sunita Hemani, Ankita Shah, Kirti Nagar, Anita Simlot (RUHS Journal of Health Sciences)
Introduction -Pregnancy is a crucial part of a females life. The prevention and early detection of adverse pregnancy outcomes are of great significance The study aimed to examine the association of low pregnancy associated plasma protein-A (PAPP-A) in the first trimester with adverse maternal and perinatal outcomes. Methodology- A total of 180 consecutive pregnant women between 11 and 13 6 weeks of pregnancy were recruited. Blood samples were taken and PAPP-A levels were analyzed based on results of PAPP-A test women were categarized into group 1 and group 2. These women were followed up for and the outcome information regarding development of hypertensive disease of pregnancy (HDP), gestational diabetes mellitus (GDM), preterm birth, intrauterine growth restriction (IUGR), intrauterine death (IUD), oligohydramnios, low birth weight, APGAR score, and NICU admission. Results- During the study period, 43 women had PAPP-A levels less than 0.5 multiple of median (MOM) and were considered as group 1 and 129 women with PAPP-A more than 0.5 MOM were group 2. In group 1, 9 women (20.93%) developed hypertensive disease of pregnancy as compared to 9 women (2.33%) in group 2. In group 1, 11 had preterm deliveries (25.58%) while it was only found in 7 women (5.43%) in group 2. Intrauterine growth retardation was seen in a total of 9 women, 6 from group 1 (13.95%) and 3 from group 2 (2.33%). 8 out of 43 neonates were admitted in NICU from group 1 (18.60%) while 8 out of 129 neonates were admitted (6.20%) in group 2. The incidence of HDP, IUGR, preterm birth, and NICU admission was significantly higher in group 1 as compared to group 2. Conclusion- PAPP-A in early pregnancy can serve as a marker for possible late pregnancy complications. Women with low PAPP-A should be monitored closely with the initiation of proper preventive measures and timely intervention should be done to decrease maternal and fetal complications.